Growing Caisim (Brassica juncea L.) Using Elaeisponic Production System - Yanda, Yusrian S.O.; Fahrurrozi, Fahrurrozi; Supanjani, Supanjani (Akta Agrosia, 2018)
Elaeisponic is new introducing growing technique to produce vegetables by planting it in the frond based of oil palm trees (Elaeis guineensis Jacq.). However, there was no previous report on vegetable production by using elaeisponic production system, including the use of foliar fertilizers. This study aimed to determine the optimum consentrations and frequency of foliar fertilization for caisim grown in elaesisponic production system. An experiment was conducted in oil palm plantation area by using a factorial randomized complete block design with three replicates. The first factor of treatment consisted of three levels of foliar fertilizer concentration, 1 g l-1, 2 g l-1 and 3 g l-1, and the second factor was application frequency of foliar fertilizer, 7 days after transplanting (DAT), 7, 14 DAT and 7, 14, 21 DAT. Crop responses were determined on leaf greenness (SPAD index), shoot fresh weight (g), root fresh weight (g), leaf area (cm2) and plant dry weight.  Results indicated that both concentration of foliar fertilizer and frequency of application as wells as its interaction did not significatly affect leaf greenness, leaf area, shoot fresh weight, root fresh weight and plant dry weight of caisim plants.  Further research should be addressed on optimizing the use of palm oil frond bases as growing medium for vegetable production.  Keywords: Elaeisponic Production System; Brassica juncea L; Foliar Fertilizer; Frequency of Application.